The key to everything [large type] - Luesse, Valerie Fraser (Thorndike press large print Christian romance, 2020)
"Peyton Cabot's fifteenth year will be a painful and transformative one. His father, the heroic but reluctant head of a moneyed Savannah family, has come home from WWII a troubled vet, drowning his demons in bourbon and distancing himself from his son. A tragic accident shows Peyton the depths of his parents' devotion to each other but interrupts his own budding romance with the girl of his dreams, Lisa Wallace.Struggling to cope with a young life upended, Peyton makes a daring decision: He will retrace a journey his father took at fifteen, riding his bicycle all the way to Key West, Florida. Part declaration of independence, part search for self, Peyton's journey will bring him more than he ever could have imagined--namely, the key to his unknowable father, a reunion with Lisa, and a calling that will shape the rest of his life.Through poignant prose and characters so real you'll be sure you know them, Valerie Fraser Luesse transports you to the storied Atlantic coast for a unique coming-of-age story you won't soon forget. ("--